Enhancing pharmacovigilance through patient engagement: perspectives and strategies - M. Younus, Manal (Pharmakeftiki, 2025)
Pharmacovigilance, as defined by the World Health Organization, is the science and activities related to the detection, assessment, understanding, and prevention of adverse events or any other possible drug-related problem. The Council for International Organizations of Medical Sciences Working Group XI has provided a comprehensive definition of patient engagement, highlighting mechanisms related to patient engagement such as direct patient reporting of adverse events, patient advisory roles, and established feedback channels. In recent years, patient roles in different aspects of healthcare, including medicine development, regulations, and the safe use of medicines are witnessing increased attention and expansion. This presentation sheds light on the importance of engaging patients in different pharmacovigilance activities, discusses patient engagement mechanisms contributing to drug safety, and addresses the strategies and the challenges associated with enhancing patient engagement.